Method for carrying out catalytic deoxidation on biological oil under hydrogen-free condition
By using multi-metallic composite catalyst Cuni@H-SiO2 during the use of biological oil dehydration, the problem of low catalyst activity and high hydrogen consumption is solved, an efficient and stable deoxygen response is achieved, and the risk of environmental pollution is reduced.
Patent Information
- Application Number
- CN202411710080.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-24
AI Technical Summary
There are problems such as low catalyst activity, high hydrogen consumption, and easy aggregation and inactivation of active metals during the deoxygenation of existing biomass oils, and there is a risk of environmental pollution.
The multi-metal composite catalyst CuNi@H-SiO2 is used to perform catalytic deoxidation under hydrogen-free conditions. The SiO2-coated core-shell structure inhibits the aggregation of active metals and improves the stability of the catalyst.
It improves the stability and reusability of the catalyst, reduces hydrogen consumption, and enhances the selectivity of alkanes, especially the total selectivity of pentadecane and hexadecane reaching 99%, while avoiding environmental pollution.
Smart Images

Figure CN119351133A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass oil deoxygenation, and in particular relates to a method for catalytic deoxygenation of bio-oil under hydrogen-free conditions. Background Art
[0002] Energy is the material basis of human activities and has greatly promoted the development of human civilization. The current main energy carriers are non-renewable fossil energy such as coal, oil and natural gas. However, the large-scale exploitation and utilization of fossil energy will not only make humans face the situation of no fossil energy available in the future, but also the problem of greenhouse gas emissions generated by its combustion is becoming more and more serious. Therefore, seeking effective utilization of renewable resources has become a consensus around the world. Renewable energy includes biomass energy, solar energy, hydropower, wind energy and geothermal energy. Among them, biomass is the only renewable carbon resource on the earth, which has the characteristics of easy access and carbon neutrality. Therefore, the development of biomass-based liquid fuels is crucial to reducing the proportion of fossil fuels in energy consumption, improving the energy structure, and promoting the sustainable development of energy.
[0003] Against the backdrop of the growing global climate crisis and growing energy demand, the production of alkane diesel using bio-oils as raw materials through a deoxygenation process has broad prospects. Among them, deoxygenation (DO) is an effective method for converting biomass-based oxygen-containing derivatives into high-value-added chemical products and fuels, which can greatly reduce the oxygen content of the product. Generally speaking, the DO process requires a higher hydrogen pressure to increase the hydrogen content in the reaction liquid. However, the harsh reaction conditions of high temperature and high pressure not only increase the equipment investment in the process, but also pose a great safety hazard. Therefore, choosing a green, environmentally friendly, safe and controllable alternative hydrogen donor is one of the effective ways to effectively solve the above problems.
[0004] In the existing technology, using deoxygenation reaction to reduce the oxygen content in biomass oil to improve the quality of oil products is an important means to achieve the conversion of biomass derivatives into liquid fuels. Although researchers have made many efforts and achieved certain research progress, the design and construction of efficient deoxygenation catalysts is still a core issue in biomass oil catalytic conversion technology. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the present invention provides a method for catalytic deoxygenation of bio-oils under hydrogen-free conditions. The method is expected to solve the problems of low catalyst activity, high hydrogen consumption, and easy aggregation and deactivation of active metals in the current biomass oil deoxygenation process, and is environmentally friendly, providing a theoretical basis and practical experience for the design and development of high-efficiency catalysts for the preparation of second-generation biodiesel from oils.
[0006] To achieve the above object, the present invention adopts the following technical solution: A method for catalytic deoxidation of bio-oil under hydrogen-free conditions comprises adding a multi-metal composite catalyst to the bio-oil and stirring and mixing, then carrying out a deoxidation reaction under nitrogen conditions, and then centrifuging and separating the reaction liquid to obtain a deoxidized liquid phase product.
[0007] Furthermore, the biological oil is methyl palmitate.
[0008] Furthermore, the multi-metal composite catalyst is a core-shell structure CuNi@H-SiO2 prepared by a coating method using a metal nitrate mixture and a silicon source as raw materials.
[0009] Furthermore, the preparation steps of the multi-metal composite catalyst are as follows: 1) Dissolve the metal nitrate mixture and PVP in anhydrous ethanol, stir at room temperature for 3 hours, transfer the solution into a hydrothermal reactor, and react at 180°C for 4 hours; 2) Add anhydrous ethanol, deionized water, ammonia water, and cetyltrimethylammonium bromide (CTAB) to the reaction solution of step 1) and stir for 2 h; 3) Add tetraethyl orthosilicate (TEOS) to the mixed solution of step 2), continue stirring for 48 hours, then centrifuge, wash with water, wash with alcohol, wash the resulting precipitate with water until it is neutral, and dry overnight; 4) The dried product obtained in step 3) was calcined at 500°C for 5 h in a muffle furnace, and then placed in a tubular furnace for reduction at 550°C for 3 h in a 10% H2 / Ar atmosphere, and then passivated at room temperature in a 2% O2 / He atmosphere for 12 h to obtain the multi-metal composite catalyst.
[0010] Wherein, the metal nitrate mixture in step 1) includes at least one of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O.
[0011] The materials used include, by weight: 0-3 parts of metal nitrate mixture, 0-3 parts of PVP, 1000 parts of anhydrous ethanol, 800 parts of deionized water, 17.5 parts of ammonia water, 0-4.5 parts of hexadecyltrimethylammonium bromide, and 2-10 parts of tetraethyl orthosilicate.
[0012] Furthermore, the amount of the multi-metal composite catalyst used is 1-20% of the weight of the bio-oil.
[0013] Furthermore, the deoxygenation reaction is carried out at a temperature of 300-400°C, a pressure of 0-3 MPa, and a time of 0.01-8 h.
[0014] Furthermore, the obtained liquid phase product includes one or more of hexadecane, pentadecane, hexadecanoic acid, and unsaturated olefins.
[0015] Compared with the prior art, the present invention has the following advantages: (1) The SiO2-coated core-shell catalyst used in the present invention can inhibit the aggregation and sintering of active metal nanoparticles during the reaction process, overcome the problems of high hydrogen consumption and easy aggregation and deactivation of active metals during the deoxygenation of biomass oil, improve the stability of the catalyst, and thus increase the catalyst reuse rate.
[0016] (2) The preparation method of the catalyst of the present invention is simple, does not involve precious metals, and has a relatively low cost. It exhibits high activity and alkane selectivity in the deoxygenation of bio-oils, with the total selectivity of pentadecane and hexadecane reaching as high as 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a comparison chart of the activity test results of catalytic deoxygenation of methyl palmitate under hydrogen-free conditions using different catalysts obtained in Examples 1 to 7. DETAILED DESCRIPTION
[0018] A method for catalytic deoxygenation of bio-oil under hydrogen-free conditions, comprising the following steps: 1) Dissolve 0-3 parts of metal nitrate mixture and 0-3 parts of PVP in 400 mL of anhydrous ethanol by weight and stir at room temperature for 3 hours; 2) After the solution in step 1) is clarified, the solution is transferred into a hydrothermal reactor, reacted at 180°C for 4 hours, and naturally cooled to room temperature; 3) Pour the reaction solution obtained in step 2) into a 5L beaker, add 1000 parts of anhydrous ethanol, 800 parts of deionized water, 0-4.5 parts of CTAB and 17.5 parts of ammonia water in sequence, stir for 2 h to mix evenly, then add 2-10 parts of TEOS dropwise, and continue stirring for 48 h; 4) After the mixed solution obtained in step 3) is centrifuged, washed with water and washed with alcohol, the obtained precipitate is washed with water until neutral, placed in a 90°C oven for drying overnight, and then calcined in a muffle furnace at 500°C for 5 h, and further placed in a tubular furnace, reduced at 550°C for 3 h in a 10% H2 / Ar atmosphere, cooled to room temperature, and then introduced with 2% O2 / He, and passivated for 12 h to obtain a core-shell structured CuNi@H-SiO2 multi-metal composite catalyst; 5) Add 1-20% by weight of a core-shell structured CuNi@H-SiO2 multi-metal composite catalyst to methyl palmitate, stir and mix, and then react under nitrogen conditions at 300-400 °C and 0-3 MPa pressure for 0.01-8 h, then centrifuge the reaction solution and separate the liquid to obtain a deoxygenated liquid product and the multi-metal composite catalyst.
[0019] Wherein, the metal nitrate mixture includes at least one of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O.
[0020] In order to make the contents of the present invention easier to understand, the technical solutions of the present invention are further clearly and completely described below in conjunction with the accompanying drawings and specific implementation methods. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0021] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0022] Example 1 Cu1Ni 0.8 The preparation of @H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 1.044 g Cu(NO3)2·3H2O, 1.006 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol after centrifugation, and then washed with water until neutral, dried in a 90°C oven overnight, and then calcined in a muffle furnace at 500°C for 5 h. It was further reduced in a tubular furnace at 550°C for 3 h in a 10% H2 / Ar atmosphere. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell multi-metal composite catalyst, denoted as Cu1Ni 0.8 @H-SiO2.
[0023] Example 2 The preparation of Cu1Ni2@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 0.602 g Cu(NO3)2·3H2O, 1.448 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol, and then washed with water until neutral, dried in a 90°C oven overnight, and then calcined at 500°C in a muffle furnace for 5 h. It was further reduced at 550°C in a tubular furnace under a 10% H2 / Ar atmosphere for 3 h. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell structured multi-metal composite catalyst, denoted as Cu1Ni2@H-SiO2.
[0024] Example 3 The preparation of Cu1Ni1@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 0.93 g Cu(NO3)2·3H2O, 1.12 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol, and then washed with water until neutral, dried in a 90°C oven overnight, and then calcined at 500°C in a muffle furnace for 5 h. It was further reduced at 550°C in a tubular furnace under a 10% H2 / Ar atmosphere for 3 h. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell structured multi-metal composite catalyst, denoted as Cu1Ni1@H-SiO2.
[0025] Example 4 Cu 0.8 The preparation of Ni1@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 0.818 g Cu(NO3)2·3H2O, 1.232 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol after centrifugation, and then washed with water until neutral, dried in a 90°C oven overnight, and then calcined in a muffle furnace at 500°C for 5 h. It was further reduced in a tube furnace at 550°C for 3 h in a 10% H2 / Ar atmosphere. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell multi-metal composite catalyst, denoted as Cu 0.8 Ni1@H-SiO2.
[0026] Example 5 The preparation of Cu2Ni1@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 1.28 g Cu(NO3)2·3H2O, 0.77 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol, and then washed with water until neutral, dried in an oven at 90°C overnight, and then calcined at 500°C for 5 h in a muffle furnace. It was further reduced at 550°C for 3 h in a tubular furnace under a 10% H2 / Ar atmosphere. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell multi-metal composite catalyst, denoted as Cu2Ni1@H-SiO2.
[0027] Comparative Example 1 The preparation of Cu@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 1.044 g Cu(NO3)2·3H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol, and then washed with water until neutral, dried in a 90°C oven overnight, and then calcined at 500°C in a muffle furnace for 5 h. It was further reduced at 550°C in a tubular furnace under a 10% H2 / Ar atmosphere for 3 h. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell structured multi-metal composite catalyst, denoted as Cu@H-SiO2.
[0028] Comparative Example 2 The preparation of Ni@H-SiO2 core-shell structure multi-metal composite catalyst includes the following steps: (1) Weigh 1.006 g Ni(NO3)2·6H2O and 2.05 g PVP and dissolve them in 400 mL anhydrous ethanol. Stir at room temperature for 3 h. (2) After the solution is clarified, it is transferred to a 1L hydrothermal reactor and subjected to hydrothermal reaction at 180°C for 4 h, followed by natural cooling to room temperature; (3) Pour the obtained suspension into a 5L beaker, add 1000g of anhydrous ethanol, 800g of deionized water, 0.35g of CTAB and 70mL of ammonia water (purity 25%) in sequence, stir for 2h to mix evenly, then add 5g of TEOS dropwise into the above solution and continue stirring for 48h; (4) After the reaction, the precipitate was washed with water and alcohol, and then washed with water until neutral, dried in an oven at 90°C overnight, and then calcined at 500°C for 5 h in a muffle furnace. It was further reduced at 550°C for 3 h in a tubular furnace under a 10% H2 / Ar atmosphere. After cooling to room temperature, 2% O2 / He was introduced and passivated for 12 h to obtain a core-shell structured multi-metal composite catalyst, denoted as Ni@H-SiO2.
[0029] Application Example 1 Accurately weigh 12g of methyl palmitate, 0.6g of catalyst Cu1Ni 0.8 @H-SiO2 was added to a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), sealed, replaced with high-purity nitrogen three times, pressurized to 1MPa, heated to 360°C, and reacted for 8h. After the reaction, the reaction liquid was centrifuged to obtain a liquid product and a solid catalyst.
[0030] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were 53.2%, 23.1% and 12.7%, respectively.
[0031] Application Example 2 Accurately weigh 12g of methyl palmitate and 0.6g of catalyst Cu1Ni2@H-SiO2, add them into a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), seal, replace with high-purity nitrogen three times, pressurize to 1MPa, heat to 360℃, and react for 8h. After the reaction, centrifuge the reaction liquid to obtain a liquid product and a solid catalyst.
[0032] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were measured to be 91.5%, 45.5% and 26.9%, respectively.
[0033] Application Example 3 Accurately weigh 12g of methyl palmitate and 0.6g of catalyst Cu1Ni1@H-SiO2, add them into a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), seal it, replace it with high-purity nitrogen three times, pressurize it to 1MPa, heat it to 360℃, and react for 8h. After the reaction, centrifuge the reaction liquid to obtain a liquid product and a solid catalyst.
[0034] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were measured to be 90.8%, 40.8% and 20.0%, respectively.
[0035] Application Example 4 Accurately weigh 12g of methyl palmitate, 0.6g of catalyst Cu 0.8 Ni1@H-SiO2 was added to a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), sealed, replaced with high-purity nitrogen three times, pressurized to 1MPa, heated to 360°C, and reacted for 8h. After the reaction, the reaction liquid was centrifuged to obtain a liquid product and a solid catalyst.
[0036] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were measured to be 91.8%, 35.4% and 16.2%, respectively.
[0037] Application Example 5 Accurately weigh 12g of methyl palmitate and 0.6g of catalyst Cu2Ni1@H-SiO2, add them into a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), seal, replace with high-purity nitrogen three times, pressurize to 1MPa, heat to 360℃, and react for 8h. After the reaction, centrifuge the reaction liquid to obtain a liquid product and a solid catalyst.
[0038] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were 37.5%, 13.4% and 12.3%, respectively.
[0039] Application Comparative Example 1 Accurately weigh 12g of methyl palmitate and 0.6g of catalyst Cu@H-SiO2, add them into a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), seal, replace with high-purity nitrogen three times, pressurize to 1MPa, heat to 360℃, and react for 8h. After the reaction, centrifuge the reaction liquid to obtain a liquid product and a solid catalyst.
[0040] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were 62.1%, 4.7% and 37.1%, respectively.
[0041] Application Comparative Example 2 Accurately weigh 12g of methyl palmitate and 0.6g of catalyst Ni@H-SiO2, add them into a 50mL high-pressure reactor (without adding additional hydrogen and hydrogen-donating solvent), seal, replace with high-purity nitrogen three times, pressurize to 1MPa, heat to 360℃, and react for 8h. After the reaction, centrifuge the reaction liquid to obtain a liquid product and a solid catalyst.
[0042] 0.1 mL of the liquid product was filtered into a sample bottle, and 1.5 mL of methyl acetate solvent was added to mix and dilute the mixture for component analysis. The conversion rate of methyl palmitate and the yields of pentadecane and hexadecane were 61.5%, 35.9% and 13.2%, respectively.
[0043] Table 1 Oil deoxidation activity of different catalysts
[0044] From the results in Table 1, it can be seen that without adding any additional hydrogen source, different metal components and their ratios have a great influence on the deoxidation performance of oils and fats. 16 Mainly, C 15The yield is low. In addition, some unsaturated olefins still exist in the liquid phase product. When metal Ni is added, the conversion rate and product distribution of methyl palmitate are quite different from those of Cu@H-SiO2 single metal catalyst. When the Cu / Ni ratio is 2 / 1, the conversion rate of methyl palmitate is low. 15 and C 16 The yields of methyl palmitate and the reaction conditions of Cu2Ni1@H-SiO2 catalysts were similar, indicating that the addition of metal Ni promoted the DCO / DCO2 process of methyl palmitate, that is, the deoxygenation reaction pathways of fats and oils were different for Cu and Ni metal catalysts. The significant decrease in the conversion rate and product yield of methyl palmitate can be attributed to the change in the Cu content in the Cu2Ni1@H-SiO2 catalyst. Further increasing the content of metal Ni, Cu1Ni 0.8 The conversion rate of methyl palmitate over the H-SiO2 catalyst was as high as 91.5%. When the Cu / Ni ratio was reduced to 1 / 1 and 0.8 / 1, the conversion rate of methyl palmitate changed little, but the yield of hexadecanoic acid in the liquid product increased, which was much higher than that of Cu1Ni. 0.8 When Ni@H-SiO2 single metal is used as catalyst, the product is C 15 In addition, compared with the CuNi bimetallic catalyst, the yield of hexadecanoic acid in the liquid phase product of the Ni monometallic catalyst is very low, indicating that hexadecanoic acid mainly comes from the Cu-catalyzed MP hydrogenolysis reaction, while the Ni metal active component catalyzes the MP to undergo DCO / DCO2 reaction.
[0045] The prepared Cu1Ni 0.8 The activity of @H-SiO2 core-shell structure catalyst was tested at different times. The specific operation is as follows: methyl palmitate was used as biomass oil raw material, its addition amount was 12.0 g, the catalyst input amount was 0.6 g, the reaction pressure was 1 MPa N2, the reaction temperature was 380℃, and the reaction times were 0, 0.25, 0.5, 1, 3, 5, and 8 h, respectively. The test results are shown in Table 2.
[0046] Table 2 Oil deoxidation activity at different reaction times
[0047] It can be seen from Table 2 that when the reaction time is extended from 0 h to 5 h, Cu1Ni 0.8 The deoxygenation performance of the @H-SiO2 bimetallic catalyst was significantly improved, and the conversion rate of methyl palmitate increased from 8.7% to 99.3%. After 5 hours of reaction, the yield of hexadecanoic acid decreased to 0.9%. In addition, due to the limited amount of in-situ hydrogen production of methyl in methyl palmitate catalyzed by the catalyst, it was unable to generate enough H2 for olefin hydrogenation reaction, and some unsaturated olefin products were still retained in the product.
[0048] Cu1Ni 0.8The activity of @H-SiO2 core-shell structure catalyst was tested at different temperatures. The specific operation is as follows: methyl palmitate was used as biomass oil raw material, its addition amount was 12.0 g, the catalyst input amount was 0.6 g, the reaction pressure was 1MPa N2, the reaction time was 8h, and the reaction temperatures were 320℃, 340℃, 360℃, and 380℃ respectively. The test results are shown in Table 3.
[0049] Table 3 Oil deoxidation activity at different reaction temperatures
[0050] It can be seen from Table 3 that under the same reaction time, as the reaction temperature increases, the conversion rate of methyl palmitate and the product yield gradually increase. When the reaction temperature is 320°C, the conversion rate of methyl palmitate is low, while the selectivity of hexadecanoic acid is high. As the reaction temperature increases, the yield of the intermediate product hexadecanoic acid shows a decreasing trend. Under different reaction temperatures, C 16 / C 15 The yield ratio of C gradually decreased, indicating that the increase in reaction temperature is conducive to the decarbonylation / decarboxylation reaction. 15 The generation rate increases.
[0051] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for catalytic deoxygenation of bio-oil under hydrogen-free conditions, characterized in that: A multi-metal composite catalyst is added to the bio-oil and stirred and mixed, and then a deoxygenation reaction is carried out under nitrogen conditions. After that, the reaction liquid is centrifuged and separated to obtain a deoxygenated liquid phase product.
2. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 1, characterized in that: The biological oil is methyl palmitate.
3. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 1, characterized in that: The multi-metal composite catalyst is a core-shell structure CuNi@H-SiO2 prepared by a coating method using a metal nitrate mixture and a silicon source as raw materials.
4. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 3, characterized in that: The preparation steps of the multi-metal composite catalyst are as follows: 1) Dissolve the metal nitrate mixture and PVP in anhydrous ethanol, stir at room temperature for 3 hours, transfer the solution into a hydrothermal reactor, and react at 180°C for 4 hours; 2) Add anhydrous ethanol, deionized water, ammonia water and hexadecyltrimethylammonium bromide to the reaction solution of step 1) and stir for 2 hours; 3) Add tetraethyl orthosilicate to the mixed solution of step 2), continue stirring for 48 hours, then centrifuge, wash with water, wash with alcohol, wash the resulting precipitate with water until it is neutral, and dry overnight; 4) The dried product obtained in step 3) was calcined at 500°C for 5 h in a muffle furnace, and then placed in a tubular furnace for reduction at 550°C for 3 h in a 10% H2 / Ar atmosphere, and then passivated at room temperature in a 2% O2 / He atmosphere for 12 h to obtain the multi-metal composite catalyst.
5. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 4, characterized in that: Step 1) The metal nitrate mixture includes at least one of Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O.
6. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 4, characterized in that: The materials used include, by weight: 0-3 parts of metal nitrate mixture, 0-3 parts of PVP, 1000 parts of anhydrous ethanol, 800 parts of deionized water, 17.5 parts of ammonia water, 0-4.5 parts of hexadecyltrimethylammonium bromide, and 2-10 parts of tetraethyl orthosilicate.
7. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 1, characterized in that: The dosage of the multi-metal composite catalyst is 1-20% of the weight of the bio-oil.
8. The method for catalytic deoxygenation of bio-oil under hydrogen-free conditions according to claim 1, characterized in that: The deoxidation reaction is carried out at a temperature of 300-400°C, a pressure of 0-3 MPa, and a time of 0.01-8 h.